Association between visceral adiposity index and all-cause and cardiovascular mortality in the non-elderly adults - Zhang, Jiqian; Li, Ming; Wang, Tongxin; Tian, Wende; Ju, Jianqing; Xu, Hao (Frontiers in Endocrinology, 2025)
BackgroundThe visceral adiposity index (VAI) reflects changes in visceral adipose function and is also linked to cardiometabolic risk. The study aimed to investigate the association between VAI and both all-cause mortality and cardiovascular mortality in the U.S. population aged 20-65 years.MethodsThis study included data from 9,094 American adults aged 20-65 years from the 2009-2018 National Health and Nutrition Examination Survey (NHANES). The exposure variable was VAI, while the outcome variables were all-cause and cardiovascular mortality. The Cox regression model was employed to explore the correlation between VAI and mortality among participants. Restricted cubic splines (RCS) were used to explore the nonlinear associations, and a two-piecewise Cox proportional hazards model was applied on both sides of the inflection point. We used subgroup analyses and interaction tests to further investigate the association between VAI and mortality in different populations. Additionally, time-dependent Receiver Operating Characteristic (ROC) curve analyses were performed to evaluate the capability of VAI in forecasting survival.ResultsDuring a median follow-up period of 74 months, 251 deaths from all causes and 50 cardiovascular-related deaths were recorded. RCS analyses did not find a nonlinear correlation between VAI and all-cause mortality (P for overall = 0.0006, P for nonlinear = 0.9927) but showed a nonlinear correlation with cardiovascular mortality (P for overall = 0.0010, P for nonlinear = 0.0062). For cardiovascular mortality, when VAI was below the threshold value (2.49), a significant positive association was observed with cardiovascular mortality. When VAI was below 2.49, the risk of cardiovascular mortality increased by 122 percent for each unit increase in VAI (HR=2.22, 95% CI:1.36-3.61). For VAI ≥ 2.49, changes in VAI did not significantly impact cardiovascular mortality risk. In subgroup analyses, the stratified results remained consistent, with no significant interactions observed in any of the subgroups (all P for interaction> 0.05). Furthermore, the areas under the curve (AUC) for 2-, 5-, and 10-year survival rates were 0.82, 0.80, and 0.79 for all-cause mortality and 0.86, 0.86, and 0.82 for cardiovascular mortality, respectively.ConclusionVAI was found to have a positive association with all-cause mortality and a nonlinear association with cardiovascular mortality in the non-elderly adults, with a threshold value of 2.49 for cardiovascular mortality.